Silkworm strains that can be clearly destined towards either embryonic diapause or direct development by adjusting a single ambient parameter during the preceding generation. Issue 4 (11th February 2014) - Egi, Yuichi; Akitomo, Shion; Fujii, Tsuguru; Banno, Yutaka; Sakamoto, Katsuhiko
Abstract In the silkworm, Bombyx mori (Lepidoptera: Bombycidae), embryonic diapause is under maternal control and the decision between diapause and direct development in bivoltine strains depends on environmental factors such as temperature and photoperiod experienced by the preceding generation. We reared ten bivoltine silkworm strains (c10, g32, k06, n25, p21, p22, p24, p44, p50 and p63) under various thermal and light conditions and examined the incidence of embryonic diapause in the next generation to identify strains in which the incidence of diapause can be controlled within the range of 0 to 100% by adjusting a single ambient parameter. Some strains were clearly destined towards either diapause or direct development. The diapause incidence in the c10, p22 and p50 strains was controlled by temperature during the egg stage (0% at 18°C and 100% at 25°C), that in the p50 strain was also determined to be dependent on illumination during the egg stage (0% under continuous darkness and 100% under continuous illumination), and photoperiod during the larval stage regulated diapause in p44 and p50 (0% and 100% under long‐day and short‐day photoperiod, respectively), when all other external parameters remained constant under each experimental condition. These diapause‐controllable silkworm strains might serve as model systems for studies of insect diapause, especially for the differential screening of related factors.